John Heil : Symposium on his Ontological Point of View. - Esfeld, Michael (Metaphysical research., 2006)
Fifty years after Willard Van Orman Quine published From a logical point of view (1953), John Heil brought out his book 'From an ontological point of view' (2003). The title expresses the shift in contemporary philosophy from logical and epistemological concerns to metaphysics. The papers of this symposium discuss that shift, focussing on what John Heil calls 'ontological seriousness', truth-making, levels of being, properties, powers, and reductionism. Each paper is followed by a comment from John Heil. The volume covers a number of the most hotly debated issues in today's metaphysics and mov.